Characterizing Biaxially Stretched Polypropylene / Graphene Nanoplatelet Composites - Mayoral, B.; Menary, G; Martin, P; Garrett, G; Millar, B; Douglas, P; Khanam, N.; AlMaadeed, M. A.; Ouederni, M.; Hamilton, A.; Sun, D. (Frontiers in Materials, 2021)
In this work, polypropylene (PP) nanocomposites containing different concentration of graphene nanoplatelets (GNPs) were prepared by melt-mixing using an industrial-scale, co-rotating, intermeshing, twin-screw extruder. The materials were then compression moulded into sheets, and biaxially stretched at different ratios (SRs) below the PP melting temperature. The effects of GNPs content and biaxial stretching on the bulk properties of PP/GNPs nanocomposites have been investigated in details. Results show that the addition of GNPs (> 5 vol%) can lead to electrically conductive composites due to the formation of percolation network. The GNPs have led to increased polymer crystallinity and enhanced materials stiffness and strength. Biaxial stretching process further enhances the materials mechanical properties but has less influence the composites electrical conductivity. The PP/GNP nanocomposites were also processed into 3D demonstrator parts using vacuum forming, and the properties of which were comparable with biaxially stretched composites.